The Right of The Human to Achieve Justice in the Saudi Judiciary - Abdullah Abdulrahman Al-Subhi (Yuridika, 2023)
Amid the crises and security, economic, and social challenges facing humanity today, the judiciary is considered a safety valve in the area of crime prevention, achieving security and stability, reassurance, and prosperity. A human's right to achieve and establish justice can only be realized through the existence of judicial institutions, as justice and judiciary are intertwined - there can be no justice without judiciary, and no judiciary without justice. If justice is lost, the judiciary loses its importance, power, and people will no longer trust it or view it to obtain their rights. Therefore, this paper comes in this conference to shed light on the most prominent pillars for achieving justice in the Saudi judiciary as a human right, and the adequacy of these pillars. My study will rely on the descriptive research method for its suitability in analyzing the provisions and regulations governing the Saudi judiciary, and to derive theoretical and practical conclusions in this context.